Use of the new Lake Louise Criteria improves CMR detection of atypical forms of acute myocarditis - Cundari, Giulia (Int J Cardiovasc Imaging, 2020)
The purpose of our study was to compare diagnostic performance of old and new Lake Louise Criteria (oLLC and nLLC) among different clinical presentations: infarct-like (IL), cardiomyopathic (CM) and arrhythmic (AR). 102 patients with clinical suspicion of acute myocarditis underwent cardiac magnetic resonance (CMR) on a 1.5 T scanner. Protocol included cine-SSFP, T2-weighted STIR, T2 mapping, early and late gadolinium enhancement and T1 mapping acquired before and after gadolinium administration. The degree of agreement has been calculated with Cohen’s K test. 42 patients also underwent endomyocardial biopsy (EMB). IL onset was present in 54/102 patients, CM in 28/102 and AR in 20/102. nLLC were positive in 58.3% of the patients, while oLLC in 37.9%, k = 0.57 (IC: 0.428–0.713). The degree of agreement between nLLC and oLLC was 0.49 (IC: 0.111–0.876) for AR onset (nLLC positive in 35% vs oLLC in 15%), 0.25 (IC: 0.035–0.459) for CM pattern (nLLC positive in 60.7% vs oLLC 17.9%) and 0.73 (IC: 0.543–0.912) for IL presentation (nLLC positive in 66.7% vs oLLC in 57.4%). Diagnostic accuracy was 75% for both nLLC and oLLC among IL onset, and 41.6% for oLLC vs 66.7% for nLLC, as regards CM clinical presentation. nLLC have improved diagnostic performance of CMR for the diagnosis of acute myocarditis, in particular for atypical clinical presentation.